Assessing the relationship between anthropometric factors and refractive errors in school-age children: height, weight, or BMI? - Risnanda, Muhammad Rafi; Anandita, Nanda Wahyu; Koentartiwi, Dyahris; Wulandari, Lely Retno (Pediatric Sciences Journal, 2024)
Introduction: Refractive errors (RE) are the leading cause of visual impairment and disability among children globally. Limited research exists on the relationship between anthropometric measures and refractive errors. This study aims to determine the correlation between weight, height, body mass index (BMI), and refractive errors in children. Methods: This cross-sectional study employed purposive sampling in orphanages across Malang City. Participants were selected based on specific inclusion criteria. Data on their weight, height, BMI, and types of refractive errors were collected as ordinal data. Refractive errors were measured objectively using an auto-refractometer, categorizing refractive errors as myopia and hyperopia based on spherical equivalent results. To minimize subjective bias, we utilized a large sample size and established clear inclusion and exclusion criteria. Additionally, we defined operational definitions for each standardized measurement to ensure consistency and accuracy. Statistical analyses were conducted using an unpaired T-test and Spearman’s correlation test with SPSS software. Results: A total of 362 participants aged 5–18 were included in the study, with 284 participants diagnosed with myopia and 78 with hyperopia. No significant differences were observed in mean body weight, height, or BMI between the myopia and hyperopia groups. Spearman's correlation test indicated no significant relationship between refractive errors and body weight (p > 0.05), height (p > 0.05), or BMI (p > 0.05). Conclusion: The study found no significant correlation between anthropometric status and the presence of refractive errors in children. Future research should consider more diverse settings and explore additional risk factors contributing to the prevalence of refractive abnormalities in children.